Effects of adding beef tallow to diets with sorghum-based dried distillers grains with solubles on growth performance and carcass characteristics in finishing pigs - Feoli, C.; Issa, S.; Gugle, Terry L.; Carter, S.D.; Cole, N.A.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 112 barrows (average weight of 158 lb) were used in a 65-d growth assay to determine the effects of adding beef tallow (a source of saturated fat) into diets with high inclusion of dried distillers grains with solubles (DDGS). The pigs were sorted by ancestry and blocked by weight with seven pigs/pen and four pens/treatment. Treatments were a corn-soybean, meal-based control and diets having 40% DDGS (US Energy Partners, Rus-sell, KS) with none, 2.5, and 5% added tallow. Feed and water were consumed on an ad libitum basis until the pigs were slaughtered (average wt of 287 lb) to allow collection of carcass data and jowl samples. Fatty acid composition of the jowl samples was used to calculate iodine value as an indicator of carcass fat firmness. Overall (d 0 to 65), the corn-soy control supported greater ADG (P< 0.03) and ADFI (P<0.001) with no difference in F/G (P>0.35) compared to the DDGS treatments. Increasing fat additions from none to 5% in diets with DDGS did not affect ADG (P>0.76) but improved (linear effect, P<0.03) F/G by 9%. As for carcass data, adding DDGS to diets reduced HCW (P<0.004) and dressing percentage (P<0.03) but increased iodine value of jowls (P<0.001) compared to pigs fed the corn-based control diet. Among the DDGS treatments, hot carcass weight (linear increase, P<0.07), dressing percentage (linear increase, P<0.07), and backfat thickness (quadratic decrease, P<0.08) responded positively as fat addition to the diets was increased from none to 5%. However, changes in iodine value indicated a trend for deposition of softer fat in pigs fed DDGS when additions of beef tallow were increased in the diet (linear effect, P<0.06). In conclusion, adding beef tallow to diets with DDGS improved efficiency of growth and several carcass measurements but did not improve iodine value of jowl fat.
Keywords: Swine; DDGS; Feed ingredient; Meat quality; Sorghum